A science of concord: the politics of commercial knowledge in mid-eighteenth-century Britain. Issue 2 (3rd April 2021) - Cooper, Jon
ABSTRACT: This article recovers mid-century proposals for sciences of concord and contextualizes them as part of a broader politics of commercial knowledge in eighteenth-century Britain. It begins by showing how merchants gained authority as formulators of commercial policy during the Commerce Treaty debates of 1713–1714. This authority held fast during the Walpolean oligarchy, but collapsed by the 1740s, when lobbying and patronage were increasingly maligned as corrupt by a ferment of popular republicanism. The article then explores how the Anglican cleric Josiah Tucker and country pamphleteer Joseph Massie made use of this vacuum in authority to formulate a novel basis for the production of commercial knowledge. In pamphlets written between 1749 and 1760, they argued that the competing interests comprising the nation's increasingly complex commercial system could only be reconciled and geared to the national interest through the establishment of a science which harnessed an impartial and systematizing epistemology, developing highly idealized accounts of the abstract market as a realm of concord which operated according to regular, rationally deducible principles. The conclusion suggests that their arguments introduced the foundational conceptual bases for later sciences of political economy and legitimated a new form of expertise in statecraft.